Teaching Moral Character Through Hadith: Pedagogical Methods In Islamic Schools - Sofia Martínez; Javier Fernandez (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This research examines how hadith literature is utilized in teaching moral and ethical character in Islamic schools. Through a case study approach involving schools in Pakistan, the study analyzes teaching methodologies that emphasize character development, kindness, honesty, and responsibility through hadith. Results show that students engaged with hadithbased moral lessons exhibit notable improvement in behavioral traits, suggesting the importance of hadith as a primary source in character education. The study provides recommendations for educators to integrate hadith effectively into characterbuilding lessons.